PENGARUH PENERAPAN MODEL KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA MATERI KELILING DAN LUAS BANGUN DATAR KELAS IV SEKOLAH DASAR - Azhari, Mery; Ahmad, Syafri (Universitas Negeri Padang, 2021)
This study aims to determine the effect of the application of the jigsaw type cooperative model to the learning outcomes of traveling around and flat area of grade IV elementary school. This research is a quantitative study, using Pretest-Posttest Control Group Design. The sampling technique is the Simple Random Sampling technique. Two sample classes are selected that will serve as the experimental and control classes. Learning compared is learning with a Jigsaw Cooperative approach with learning using a conventional approach. Data collection techniques are test instruments. Tests are given namely on the circumferential material and flat area in the form of objective questions. Data were analyzed using t-test. t arithmetic> t table, then H0 is rejected and Ha is accepted, that is tcount> t table which is 3.235> 2.011 means Ha is accepted and H0 is rejected. It was concluded that there were differences in student learning outcomes using the Jigsaw Cooperative Learning model with student learning outcomes using the conventional approach to learning to get up and down in class IV Elementary School.